Characteristics and In‐Hospital Outcomes of Patients With Septic Shock in the Adult Medical Intensive Care Unit of a Tertiary Hospital in Ethiopia: A Prospective Observational Study - Amanuel Zeleke; Gashaw Solela; Alazar Sitotaw; Balew Arega; Elias Tewabe; Haileyesus Teshome; Hanna Alemu; Seble Legese; Sebrina Ahmed; Selam Gissa; Simret Alemu; Anteneh Mitiku; et al. (Health Science Reports)
ABSTRACT Background and Aims Sepsis and septic shock are major healthcare problems, affecting millions of people around the world each year and claiming the lives of one‐sixth to one‐third of those affected. However, there is insufficient data on the characteristics and outcomes of septic shock patients in resource‐limited settings. This study aimed to assess the characteristics and in‐hospital outcomes of septic shock among patients admitted to the adult medical intensive care unit (ICU) of a tertiary hospital in Ethiopia. Methods A prospective observational study was conducted among patients diagnosed with septic shock according to consensus criteria who were admitted to the adult medical ICU of a tertiary hospital in Ethiopia from January 1, 2023, to September 30, 2023. Results A total of 144 patients were included in this study, with a mean age of 46 ± 19 years. The respiratory system was the most common source of infection, affecting 70.2% of the patients. The blood culture positivity rate was 8.4%, and antibiotics were revised for only 2.8% of the patients tailored to culture results. Adrenaline was the most frequently used vasopressor (73.6%), followed by noradrenaline (27.8%). The main complications were acute kidney injury (51.4%) and acute lung injury (50.7%). The in‐hospital mortality rate was 66.7%, with a median hospital stay of 6 days (interquartile range: 2–11 days). Multivariable Cox regression analysis showed that a Glasgow Coma Scale score below 15 (AHR: 2.23; 95% CI, 1.35–3.69) and peripheral oxygen saturation under 90% (AHR: 8.74; 95% CI, 1.18–14.84) were independently associated with increased in‐hospital mortality risk. Conclusions This study demonstrated a high mortality rate among septic shock patients with more than two‐thirds of patients dying during their hospital stay. The significant prognostic indicators of in‐hospital mortality were impaired mental status and peripheral oxygen desaturation.